The Influence of Somethinc Skincare Advertising Commodification on Consumer Purchasing Desicions - Rahmawati , Neny; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to the effect of Somethinc skincare advertising commodification on consumer purchasing decisions. Commodification of communication is the process by which communication is transformed into a marketable commodity. In this context, Somethinc advertisements seek not only to market skincare products, but also to convey certain ideas, values and lifestyles to consumers. The research method used is quantitative, by circulating questionnaires to 85 respondents who are consumers of Somethinc products.The results showed that commodification in Somethinc advertising has a positive and significant influence on consumer purchasing decisions. t value (4.382) > t table (1.663). This figure indicates that H0 is rejected and Ha is accepted. There is a significant influence between commodification in Somethinc skincare advertisements on consumer purchasing decisions. The figure is 18.8%, this shows that the relationship between the independent variable and the dependent variable is in the medium correlation category. In this finding that the commodification of advertising affects the purchasing decision of somethinc skincare